Impact of CMV latency on T-cell responses to COVID-19 vaccination among predominantly antibody-deficient patients - Alba-Cano, Trinidad; Alonso, Roberto; Balastegui-Martín, Héctor; Bravo-Gallego, Luz Yadira; Sánchez-Mateos, Paloma; Martín-López, Mónica; Gil-Herrera, Juana (Frontiers in Immunology, 2025)
BackgroundThe immunogenicity of mRNA COVID-19 vaccines has been reported as highly variable in patients with inborn errors of immunity (IEI).ObjectiveThe aim of this study was to study memory CD4+ T-cell-mediated responses against the Spike (S) protein of SARS-CoV-2 along with CMV peptides in a large IEI group composed of mostly predominantly antibody-deficient (PAD) patients.Patients and methodsIn vitro antigen-specific T-cell anti-S and -CMV responses after two doses of mRNA COVID-19 vaccines were assessed in peripheral blood from 114 patients with IEI and 38 healthcare healthy controls (HCHC). Stimulation index (SI) based on the percentages of CD4+ T lymphocytes with effector memory phenotype CD45RA−CD27− (TEM) was quantified by flow cytometry.ResultsPatients with IEI overall, as well as the two main groups of PAD [i.e., common variable immunodeficiency (CVID) and isotype or functional antibody deficiencies (IOFD)], showed frequencies of responder individuals and median SI against SARS-CoV-2 comparable to HCHC. However, those IEI and CVID subgroups positive for anti-CMV T-cell immunity showed a significantly reduced response (SI) against S-peptides when compared to their IEI and CVID counterparts who were anti-CMV TEM negative. This effect of CMV stratification is independent of age in our patient group.ConclusionCMV latency negatively impacted the CD4+ TEM population’s functionality regarding COVID-19 vaccination in patients with CVID. Our results in patients with IEI and previous similar findings in healthy populations highlight the fact that when assessing immune-specific responses, the inclusion of CMV monitoring is suitable, is worthwhile, and may potentially be extended to vaccinations against different pathogens to prevent human disease more accurately.